2008
DOI: 10.1210/en.2008-0148
|View full text |Cite
|
Sign up to set email alerts
|

GATA-4 Regulates Bcl-2 Expression in Ovarian Granulosa Cell Tumors

Abstract: Excessive cell proliferation and decreased apoptosis have been implicated in the pathogenesis of ovarian granulosa cell tumors (GCTs). We hypothesized that transcription factor GATA-4 controls expression of the antiapoptotic factor Bcl-2 and the cell cycle regulator cyclin D2 in normal and neoplastic granulosa cells. To test this hypothesis, a tissue microarray based on 80 GCTs was subjected to immunohistochemistry for GATA-4, Bcl-2, and cyclin D2, and the data were correlated to clinical and histopathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 37 publications
2
74
1
Order By: Relevance
“…7,29,37,38 The latter were verified to possess the c.402C-G (p.C134W) mutation in FOXL2 5 and the mutation frequency of 95% corresponds to other published GCT series. [2][3][4] All histological diagnoses were carefully reevaluated, 29 patient charts were reviewed to obtain clinical data and recurrences were updated as of September 2009.…”
Section: Materials and Methods Human Tissue Samplesmentioning
confidence: 57%
See 1 more Smart Citation
“…7,29,37,38 The latter were verified to possess the c.402C-G (p.C134W) mutation in FOXL2 5 and the mutation frequency of 95% corresponds to other published GCT series. [2][3][4] All histological diagnoses were carefully reevaluated, 29 patient charts were reviewed to obtain clinical data and recurrences were updated as of September 2009.…”
Section: Materials and Methods Human Tissue Samplesmentioning
confidence: 57%
“…Primers listed in Table 1 were designed with IDT SciTools software or as previously described. 43,44 Western blotting of the protein samples was performed as described 38 with antibodies and dilutions listed in Table 1.…”
Section: Materials and Methods Human Tissue Samplesmentioning
confidence: 99%
“…u5SS, 3SS, 5SS and d3SS: intronic regions close to upstream exon's 5′ splice site, target exon's 3′ and 5′ splice sites, and downstream exon's 3′ splice site, respectively. npg A n A ly s i s granulosa cell tumors 38 . We analyzed all COSMIC 69 (ref.…”
Section: A N a Ly S I Smentioning
confidence: 99%
“…Given that GATA4 is an upstream regulator of BCL2 and BCLX L in some other cell types including cardiomyocytes, ovarian granulosa cell tumor cells, and lung vascular smooth muscle cells, 22,27 we hypothesized that the alterations in their expression in HUH6 cells during Dox treatment are due to a reduction in GATA4 expression. To this end, we first studied whether Dox treatment affects GATA4 levels in the human HUH6 cells.…”
Section: Gata4 Silencing Alters Expression Of Bcl2 Family Members In mentioning
confidence: 99%
“…25 Along with myocardium, GATA4 regulates BCL2 and BCLX L expression in other normal and neoplastic tissues including lung vascular smooth muscle 26 and ovarian granulosa cell tumors. 22,27 In contrast to most human cell types, normal postnatal hepatocytes lack expression of anti-apoptotic BCL2, presumably due to the slow regeneration of liver tissue. 28 It has been shown that BCL2 is, however, expressed in a subset of HBs.…”
Section: Introductionmentioning
confidence: 99%